Flexible carboxymethyl cellulose ether, preparation method thereof and battery negative electrode slurry binder
By introducing flexible chain segments on the side chains of carboxymethyl cellulose, flexible carboxymethyl cellulose ether is prepared as a binder for the negative electrode slurry of the battery, the problem of insufficient flexibility of carboxymethyl cellulose material in the prior art is solved, and the surface density and battery capacity of the negative electrode material coating are significantly improved.
Patent Information
- Application Number
- CN202510115870.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-24
- Publication Date
- 2025-04-11
AI Technical Summary
The existing carboxymethylcellulose materials are prone to cracking, wrinkles, powder loss and other defects in thick-coated electrode materials, and are insufficient in flexibility, making it difficult to significantly increase the surface density of the negative electrode material coating.
By introducing flexible chain segments, such as methoxy polyethylene glycol-ethylene oxide copolymer, C10-C16 haloalkanes, etc., on the side chain of carboxymethyl cellulose, grafting reaction, flexible carboxymethyl cellulose ether is prepared and used as a binder for the negative electrode slurry of the battery.
The surface density of the negative electrode material coating is significantly improved, the electrode sheet does not crack and warp is low during drying, the battery capacity is improved, and the problems of harsh reaction conditions, high cost and cumbersome preparation process during the modification of carboxymethyl cellulose are solved.
Smart Images

Figure CN119798686A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of negative electrode slurry binders, in particular to a flexible carboxymethyl cellulose ether and a preparation method thereof and a negative electrode slurry binder for a battery. Background Art
[0002] The negative electrode plate of the battery includes a current collector and a negative electrode material coating coated on the surface of the current collector. The negative electrode material coating includes a conductive component, an active component and a binder. Among them, the binder can firmly bond the negative electrode active material to the current collector to prevent the negative electrode material coating from falling off and stratifying, thereby ensuring the stability of the battery system. With the gradual increase in the energy density of power batteries and the development of large-scale energy storage systems, thick-coated negative electrode materials have gradually become a trend. In order to prevent the negative electrode material coating from cracking, wrinkling, powdering and other defects caused by insufficient flexibility and bonding force of the binder, thick-coated electrode materials have higher requirements on the bonding and flexibility of the binder.
[0003] Carboxymethyl cellulose material can be used as a suspension stabilizer and binder in the negative electrode plate. However, the molecular chain of carboxymethyl cellulose contains hydroxyl and carboxyl groups, and has strong intermolecular cohesion, which makes it more brittle. When it is used for thick coating electrode materials, it is prone to cracking, wrinkling, powder loss and other defects, and the effect of improving the surface density of thick coating negative electrode materials is limited. At present, the method commonly used to solve the lack of flexibility of carboxymethyl cellulose materials is to add plasticizers to the carboxymethyl cellulose materials, or to modify the carboxymethyl cellulose by esterification, grafting and other means to improve the flexibility of the carboxymethyl cellulose materials. For example, the relevant prior art discloses a lithium magnesium silicate modified carboxymethyl cellulose ether. When used as a binder for negative electrode materials, although it can increase the surface density of the negative electrode slurry coating to 136g / m 2 , but the improvement in coating surface density compared to conventional positive and negative electrode materials is still not significant. Summary of the invention
[0004] The purpose of the present invention is to provide a flexible carboxymethyl cellulose ether and a preparation method thereof and a battery negative electrode slurry binder. The flexible carboxymethyl cellulose ether provided by the present invention has excellent plasticity and flexibility. When it is used as a binder in the negative electrode slurry, the surface density of the negative electrode material coating can be significantly improved.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The invention provides a flexible carboxymethyl cellulose ether, which comprises carboxymethyl cellulose and a flexible chain segment grafted on the side chain of the carboxymethyl cellulose; the compound of the flexible chain segment comprises one of methoxy polyethylene glycol-ethylene oxide copolymer, C10-C16 halogenated alkane, 2-ethyl alkyl chloroformate, alkyl chloroformate, ethyl (2R)-2,3-epoxy resin alkyl acid, chloromethyl alkyl ether and 2-chloroalkyl chloromethyl ether.
[0007] Preferably, the grafting rate of the flexible carboxymethyl cellulose ether is 5-25%.
[0008] The present invention also provides a method for preparing the flexible carboxymethyl cellulose ether described in the above technical solution, comprising: mixing carboxymethyl cellulose, a compound of a flexible chain segment and a solvent, and performing a grafting reaction to obtain the flexible carboxymethyl cellulose ether.
[0009] Preferably, the mass percentage of the carboxymethyl cellulose in the solvent is 1-50%.
[0010] Preferably, the ratio of the mass of the carboxymethyl cellulose to the mass of the compound of the soft segment is 10:0.5-2.
[0011] Preferably, the temperature of the grafting reaction is 50-70°C.
[0012] Preferably, the grafting reaction time is 1 to 10 hours.
[0013] The present invention also provides a battery negative electrode slurry binder, wherein the binder in the battery negative electrode slurry is a flexible carboxymethyl cellulose ether or a mixture of a flexible carboxymethyl cellulose ether and a linear chain polymer material; the flexible carboxymethyl cellulose ether is the flexible carboxymethyl cellulose ether described in the above technical solution or the flexible carboxymethyl cellulose ether prepared by the preparation method described in the above technical solution.
[0014] Preferably, the linear chain polymer material includes one or more of linear polyvinyl alcohol, polyvinyl pyrrolidone and polyacrylic acid.
[0015] Preferably, the mass ratio of the flexible carboxymethyl cellulose ether to the linear chain polymer material is 10:0.1-5.
[0016] The present invention provides a flexible carboxymethyl cellulose ether, which includes carboxymethyl cellulose and a flexible chain segment grafted on the side chain of the carboxymethyl cellulose; the compound of the flexible chain segment includes one of methoxy polyethylene glycol-ethylene oxide copolymer, C10-C16 halogenated alkane, 2-ethyl alkyl chloroformate, alkyl chloroformate, ethyl (2R)-2,3-epoxy resin alkyl acid, chloromethyl alkyl ether and 2-chloroalkyl chloromethyl ether. The side chain of the flexible carboxymethyl cellulose ether provided by the present invention is grafted with a flexible chain segment, and the type of the compound of the flexible chain segment is specifically defined. The introduction of these flexible chain segments can not only make the molecular chain of carboxymethyl cellulose have a certain flexibility, but also reduce the interaction between the molecular chains of carboxymethyl cellulose, thereby improving the flexibility and plasticity of carboxymethyl cellulose. The results of the embodiment show that the flexible carboxymethyl cellulose ether provided by the present invention is applied to the negative electrode slurry of the battery, and the coating surface density is increased to 550g / m 2 The electrode does not crack during the drying process and has low warping, which can effectively achieve thick coating of the negative electrode slurry and reduce the cracking of the electrode in the later stage. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 The infrared spectra of the carboxymethyl cellulose used in Example 1 of the present invention and the prepared flexible carboxymethyl cellulose ether;
[0018] Figure 2 This is a comparison chart of the tensile strength of the film prepared from the carboxymethyl cellulose used in Example 1 of the present invention and the flexible carboxymethyl cellulose ether prepared;
[0019] Figure 3 These are photos of the copper foil used in the present invention and the copper foil coated with the flexible carboxymethyl cellulose ether prepared in Example 1, the flexible carboxymethyl cellulose ether prepared in Comparative Example 2, and carboxymethyl cellulose after drying. DETAILED DESCRIPTION
[0020] The invention provides a flexible carboxymethyl cellulose ether, which comprises carboxymethyl cellulose and a flexible chain segment grafted on the side chain of the carboxymethyl cellulose; the compound of the flexible chain segment comprises one of methoxy polyethylene glycol-ethylene oxide copolymer, C10-C16 halogenated alkane, 2-ethyl alkyl chloroformate, alkyl chloroformate, ethyl (2R)-2,3-epoxy resin alkyl acid, chloromethyl alkyl ether and 2-chloroalkyl chloromethyl ether.
[0021] In the present invention, the C10-C16 halogenated alkane is preferably decabromoane or 1-chlorohexadecane.
[0022] In the present invention, the 2-ethylalkyl chloroformate is preferably 2-ethylhexyl chloroformate.
[0023] In the present invention, the alkyl chloroformate is preferably hexadecyl chloroformate.
[0024] In the present invention, the ethyl (2R)-2,3-epoxy resin alkyl acid is preferably ethyl (2R)-2,3-epoxy resin propanoic acid.
[0025] In the present invention, the chloromethyl alkyl ether is preferably chloromethyl octyl ether.
[0026] In the present invention, the 2-chloroalkyl chloromethyl ether is preferably 2-chloroethyl chloromethyl ether.
[0027] The present invention uses the above compound as the side chain of the flexible carboxymethyl cellulose ether, which has good flexibility, not only can make the molecular chain of the flexible carboxymethyl cellulose ether have certain flexibility, but also can reduce the interaction between the molecular chains of the flexible carboxymethyl cellulose ether, and improve the flexibility of the flexible carboxymethyl cellulose ether.
[0028] In the present invention, the grafting rate of the flexible carboxymethyl cellulose ether is preferably 5-25%. In the present invention, the grafting rate of the flexible carboxymethyl cellulose ether can be 5%, 6%, 8%, 10%, 12%, 15%, 18%, 20% or 25%. The present invention controls the grafting rate of the flexible carboxymethyl cellulose ether within the above range, which is more conducive to improving the flexibility of the carboxymethyl cellulose.
[0029] The present invention also provides a method for preparing the flexible carboxymethyl cellulose ether described in the above technical solution, comprising: mixing carboxymethyl cellulose, a compound of a flexible chain segment and a solvent, and performing a grafting reaction to obtain the flexible carboxymethyl cellulose ether.
[0030] In the present invention, the solvent is preferably anhydrous ethanol or ethanol aqueous solution, and the mass percentage of ethanol in the ethanol aqueous solution is preferably 50 to 95%, more preferably 50 to 75%. The present invention uses the above solvent to promote the grafting reaction more fully.
[0031] In the present invention, the mass percentage of the carboxymethyl cellulose in the solvent is preferably 1-50%, more preferably 2-40%. The present invention controls the mass percentage of the carboxymethyl cellulose in the solvent within the above range, which makes it easier for the carboxymethyl cellulose to form a suitable concentration range and make the grafting reaction more complete.
[0032] In the present invention, the mass ratio of the carboxymethyl cellulose to the mass ratio of the compound of the soft segment is preferably 10: 0.5 to 2, more preferably 10: 1. The present invention controls the mass ratio of the carboxymethyl cellulose to the mass ratio of the compound of the soft segment within the above range, which can increase the grafting rate of the soft segment on the side chain of the carboxymethyl cellulose.
[0033] In the present invention, the method of mixing the carboxymethyl cellulose, the compound of the soft segment and the solvent is preferably: dispersing the carboxymethyl cellulose in the solvent to obtain a carboxymethyl cellulose dispersion; and then mixing the carboxymethyl cellulose dispersion with the compound of the soft segment. The present invention has no particular limitation on the method of mixing the carboxymethyl cellulose dispersion with the compound of the soft segment, and the compound of the soft segment can be dissolved in the carboxymethyl cellulose dispersion.
[0034] In the present invention, the temperature of the grafting reaction is preferably 50-70°C, more preferably 60°C; the time of the grafting reaction is preferably 1-10 hours, more preferably 2-6 hours. The present invention controls the temperature and time of the grafting reaction within the above ranges, which can promote the grafting of the flexible segment compound onto the side chain of the carboxymethyl cellulose.
[0035] The present invention preferably filters, washes and dries the system obtained by the grafting reaction in sequence after the grafting reaction to obtain flexible carboxymethyl cellulose ether. The present invention separates the solid-liquid of the system obtained by the grafting reaction by filtering. The present invention can remove the solvent in the solid and the flexible segments not grafted onto the carboxymethyl cellulose by washing. In an embodiment of the present invention, the washing reagent can be an ethanol aqueous solution, and the mass concentration of ethanol in the ethanol aqueous solution can be 80%; the number of washings can be 3 times. In the present invention, the drying temperature can be 120°C, and the drying time can be 2 hours. The present invention can remove impurities in the flexible carboxymethyl cellulose ether by filtering, washing and drying.
[0036] The preparation method provided by the present invention uses a flexible segment to modify carboxymethyl cellulose, and the etherification modification operation is simple and the conditions are easy to control. The method provided by the present invention is simple to operate and the conditions are easy to control, and can solve the problems of harsh reaction conditions, high cost, and complicated preparation process in the modification of carboxymethyl cellulose.
[0037] The present invention also provides a battery negative electrode slurry binder, wherein the binder in the battery negative electrode slurry is a flexible carboxymethyl cellulose ether or a mixture of a flexible carboxymethyl cellulose ether and a linear chain polymer material.
[0038] In the present invention, the flexible carboxymethyl cellulose ether is the flexible carboxymethyl cellulose ether described in the above technical solution, which will not be described in detail here.
[0039] In the present invention, the linear chain polymer material preferably includes one or more of linear polyvinyl alcohol, polyvinyl pyrrolidone and polyacrylic acid.
[0040] In the present invention, the weight average molecular weight of the polyvinyl alcohol is preferably Mw 9000-10000, 80-90% hydrolyzed; more preferably Mw 31000-50000, 87-89% hydrolyzed.
[0041] In the present invention, the weight average molecular weight of the polyvinyl pyrrolidone is preferably Mw8000.
[0042] In the present invention, the weight average molecular weight of the polyacrylic acid is preferably Mw500000.
[0043] The present invention adopts the above-mentioned type of linear chain polymer material, which has good compatibility with the negative electrode slurry.
[0044] In the present invention, the mass ratio of the flexible carboxymethyl cellulose ether to the linear chain polymer material is 10:0.1-5. As an embodiment of the present invention, the mass ratio of the flexible carboxymethyl cellulose ether to the linear chain polymer material can be 10:0.1, 10:0.2, 10:0.3, 10:0.4, 10:0.5, 10:0.6, 10:0.7, 10:0.8, 10:0.9, 10:1, 10:2, 10:3 or 10:5. The present invention controls the mass ratio of the flexible carboxymethyl cellulose ether to the linear chain polymer material within the above range, and can use the linear chain polymer material to weaken the force between the modified carboxymethyl cellulose molecules, thereby enhancing the flexibility and plasticity of the flexible carboxymethyl cellulose ether.
[0045] In the present invention, the preparation method of the mixture of the flexible carboxymethyl cellulose ether and the linear chain polymer material preferably includes mechanical mixing, solution mixing, vapor deposition, injection molding or gel infiltration. The present invention has no particular limitation on the specific operation methods of the mechanical mixing, solution mixing, vapor deposition, injection molding and gel infiltration, as long as the flexible carboxymethyl cellulose ether and the linear chain polymer material can be uniformly mixed.
[0046] The present invention introduces flexible chain segments with good flexibility into the side chains of carboxymethyl cellulose, which not only makes the molecular chain have a certain flexibility, but also reduces the interaction between cellulose molecular chains and improves the flexibility of carboxymethyl cellulose. The present invention utilizes linear chain polymer materials to further weaken the interaction between modified carboxymethyl cellulose molecules, further enhancing the flexibility and plasticity of carboxymethyl cellulose, so that it has excellent flexibility when used as a binder for battery negative electrode slurry.
[0047] Since the flexible carboxymethyl cellulose ether provided by the present invention has excellent flexibility and plasticity, the coating surface density of the negative electrode slurry can be improved, the pole piece will not crack during drying, the warping is low, and good processing performance is maintained, thereby further improving the battery capacity.
[0048] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0049] Raw materials and sources used in the embodiments of the present invention:
[0050] Carboxymethyl cellulose (CMC): sourced from Chongqing Lihong Fine Chemical Co., Ltd., degree of substitution DS = 0.9, viscosity η = 3000 mpa·s;
[0051] Ethylene oxide (EO): sourced from Shanghai Aladdin Biochemical Technology Co., Ltd., purity > 99.5%;
[0052] Methoxypolyethylene glycol (mPEG): Source: Shanghai Aladdin Biochemical Technology Co., Ltd. W 1000;
[0053] Polyglycerol-4-dodecyl ether, polyvinyl alcohol, decabromoethane, ethyl (2R)-2,3-epoxypropane acid and 2-ethylhexyl chloroformate were from Shanghai MacLean Biochemical Technology Co., Ltd., and polyethylene glycol was from Shanghai Aladdin Biochemical Technology Co., Ltd.
[0054] Example 1
[0055] A flexible carboxymethyl cellulose ether, wherein the flexible carboxymethyl cellulose ether is a methoxy polyethylene glycol-ethylene oxide copolymer grafted with modified carboxymethyl cellulose, and the grafting rate of the methoxy polyethylene glycol-ethylene oxide copolymer in the flexible carboxymethyl cellulose ether is 8%;
[0056] The preparation method of the flexible carboxymethyl cellulose ether is as follows: at 25°C, 150 parts of CMC are dispersed in a mixed solution of 250 parts of anhydrous ethanol and 250 parts of deionized water to obtain a cellulose dispersion; the cellulose dispersion is mixed with 1.5 parts of EO and 13.5 parts of mPEG and a solvent, and a grafting reaction is performed at 60°C for 2 hours, and then a crude flexible carboxymethyl cellulose ether is obtained by filtering, and the sample is washed three times with an 80% ethanol aqueous solution, and dried at 120°C for 2 hours to obtain the flexible carboxymethyl cellulose ether.
[0057] The carboxymethyl cellulose used in this example and the prepared flexible carboxymethyl cellulose ether (i.e. Figure 1 The infrared spectrum of the flexible carboxymethyl cellulose in Figure 1 As shown. Figure 1It can be seen that the infrared spectra of carboxymethyl cellulose and flexible carboxymethyl cellulose ether are highly consistent, indicating that the modification of carboxymethyl cellulose with EO and mPEG copolymer does not change or destroy the main structure of carboxymethyl cellulose.
[0058] The carboxymethyl cellulose used in this embodiment and the prepared modified carboxymethyl cellulose are respectively prepared into adhesive films, and the method is as follows: CMC is prepared into a 1% concentration solution, a fixed weight of the adhesive solution is weighed and introduced into a microbial culture dish, and the adhesive solution is gently shaken to level it. Then it is placed in a 50°C oven and dried at low temperature until it is completely dried. The dried product is placed in a dryer and cooled to room temperature. Take it out and let it stand in a normal environment for 30 minutes. Use tweezers to draw a circle on the wall of the culture dish, and then lift up a corner, and finally remove it along the corner to obtain the adhesive film. The obtained film is cut into 5×80mm and tested for tensile force on a universal testing machine at a speed of 100mm / min until it breaks, and the tensile strength comparison chart of the used carboxymethyl cellulose film and the modified carboxymethyl cellulose film is as shown below. Figure 2 As shown. Figure 2 In the table, BCQ refers to the tensile strength curve of carboxymethyl cellulose film, and BFCQ refers to the tensile strength curve of modified carboxymethyl cellulose film. Figure 2 It can be seen that the tensile strength of the modified carboxymethyl cellulose film is greatly improved compared with the carboxymethyl cellulose film, which shows that the modification method provided by the present invention can significantly improve the flexibility of carboxymethyl cellulose.
[0059] Example 2
[0060] A flexible carboxymethyl cellulose ether, wherein the flexible carboxymethyl cellulose ether is a methoxy polyethylene glycol-ethylene oxide copolymer grafted with modified carboxymethyl cellulose, and the grafting rate of the methoxy polyethylene glycol-ethylene oxide copolymer in the flexible carboxymethyl cellulose ether is 6%;
[0061] The preparation method of the flexible carboxymethyl cellulose ether is as follows: at 25°C, 50 parts of CMC are dispersed in a mixed solution of 250 parts of anhydrous ethanol and 250 parts of deionized water to obtain a cellulose dispersion; the cellulose dispersion is mixed with 0.5 parts of EO and 4.5 parts of mPEG, and a grafting reaction is performed at 60°C for 2 hours, and then a crude flexible carboxymethyl cellulose ether is obtained by filtering, and the sample is washed three times with an 80% ethanol aqueous solution, and dried at 120°C for 2 hours to obtain the flexible carboxymethyl cellulose ether.
[0062] Example 3
[0063] A battery negative electrode slurry binder, comprising the flexible carboxymethyl cellulose ether prepared in Example 2 and a linear chain polymer material, wherein the mass ratio of the flexible carboxymethyl cellulose ether to the linear chain polymer material is 10:0.1;
[0064] The preparation method of the battery negative electrode slurry binder is as follows: 0.1 parts of polyvinyl alcohol is dissolved in an appropriate amount of aqueous solution, mixed with 10 parts of the flexible carboxymethyl cellulose ether prepared in Example 2 by spraying, then vacuum dried at 80° C. for 2 hours, and crushed to obtain the battery negative electrode slurry binder.
[0065] Example 4
[0066] A flexible carboxymethyl cellulose ether, wherein the flexible carboxymethyl cellulose ether is carboxymethyl cellulose grafted with decabromoethane, and the grafting rate of decabromoethane in the flexible carboxymethyl cellulose ether is 6%;
[0067] The preparation method of the flexible carboxymethyl cellulose ether is as follows: at 25°C, 50 parts of CMC are dispersed in 500 parts of anhydrous ethanol to obtain a cellulose dispersion; the cellulose dispersion is mixed with 5 parts of decabromoethane, and a grafting reaction is carried out at 60°C for 2 hours, and then a crude flexible carboxymethyl cellulose ether is obtained by filtering, and the sample is washed three times with an 80% ethanol aqueous solution, and dried at 120°C for 2 hours to obtain the flexible carboxymethyl cellulose ether.
[0068] Example 5
[0069] A flexible carboxymethyl cellulose ether, wherein the flexible carboxymethyl cellulose ether is carboxymethyl cellulose grafted with 2-ethylhexyl chloroformate, and the grafting rate of 2-ethylhexyl chloroformate in the flexible carboxymethyl cellulose ether is 6%;
[0070] The preparation method of the flexible carboxymethyl cellulose ether is as follows: at 25°C, 50 parts of CMC are dispersed in 500 parts of anhydrous ethanol to obtain a cellulose dispersion; the cellulose dispersion is mixed with 5 parts of 2-ethylhexyl chloroformate, and a grafting reaction is carried out at 60°C for 4 hours, and then a crude flexible carboxymethyl cellulose ether is obtained by filtering, and the sample is washed 3 times with an 80% ethanol aqueous solution, and dried at 120°C for 2 hours to obtain the flexible carboxymethyl cellulose ether.
[0071] Example 6
[0072] A flexible carboxymethyl cellulose ether, wherein the flexible carboxymethyl cellulose ether is carboxymethyl cellulose grafted with ethyl (2R)-2,3-epoxy resin propane acid and modified, and the grafting rate of ethyl (2R)-2,3-epoxy resin propane acid in the flexible carboxymethyl cellulose ether is 8%;
[0073] The preparation method of the flexible carboxymethyl cellulose ether is as follows: at 25°C, 50 parts of CMC are dispersed in 500 parts of anhydrous ethanol to obtain a cellulose dispersion; the cellulose dispersion is mixed with 5 parts of ethyl (2R)-2,3-epoxy resin propane acid, and a grafting reaction is carried out at 60°C for 6 hours, and then a crude flexible carboxymethyl cellulose ether is obtained by filtering, and the sample is washed 3 times with an 80% ethanol aqueous solution, and dried at 120°C for 2 hours to obtain the flexible carboxymethyl cellulose ether.
[0074] Example 7
[0075] A flexible carboxymethyl cellulose ether, wherein the flexible carboxymethyl cellulose ether is a carboxymethyl cellulose grafted with a methoxy polyethylene glycol-ethylene oxide copolymer, and the grafting rate of the methoxy polyethylene glycol-ethylene oxide copolymer in the flexible carboxymethyl cellulose ether is 5%;
[0076] The preparation method of the flexible carboxymethyl cellulose ether is as follows: at 25°C, 10 parts of CMC are dispersed in a mixed solution of 250 parts of anhydrous ethanol and 250 parts of deionized water to obtain a cellulose dispersion; the cellulose dispersion is mixed with 0.15 parts of EO and 1.35 parts of mPEG and a solvent, and a grafting reaction is performed at 60°C for 2 hours, and then a crude flexible carboxymethyl cellulose ether is obtained by filtering, and the sample is washed three times with an 80% ethanol aqueous solution, and dried at 120°C for 2 hours to obtain the flexible carboxymethyl cellulose ether.
[0077] Example 8
[0078] A battery negative electrode slurry binder, comprising the flexible carboxymethyl cellulose ether prepared in Example 7 and a linear chain polymer material, wherein the mass ratio of the flexible carboxymethyl cellulose ether to the linear chain polymer material is 10:1;
[0079] The preparation method of the battery negative electrode slurry binder is as follows: dissolving 1 part of polyacrylic acid in an appropriate amount of aqueous solution, mixing it with 10 parts of the flexible carboxymethyl cellulose ether prepared in Example 7 by spraying, and then vacuum drying it at 80° C. for 2 hours, and crushing it to obtain the battery negative electrode slurry binder.
[0080] Comparative Example 1
[0081] A preparation method of flexible carboxymethyl cellulose ether comprises the following steps: at 25°C, dispersing 150 parts of CMC in a mixed solution of 250 parts of anhydrous ethanol and 250 parts of deionized water to obtain a cellulose dispersion; mixing the cellulose dispersion with 1.5 parts of EO and 13.5 parts of mPEG and a solvent, performing a grafting reaction at 60°C for 2 hours, then filtering to obtain a crude flexible carboxymethyl cellulose ether, washing the sample three times with an 80% ethanol aqueous solution, and drying at 120°C for 2 hours to obtain the flexible carboxymethyl cellulose ether.
[0082] Comparative Example 2
[0083] A flexible carboxymethyl cellulose ether, comprising carboxymethyl cellulose and a linear chain polymer material, wherein the mass ratio of the carboxymethyl cellulose to the linear chain polymer material is 10:1;
[0084] The preparation method of the flexible carboxymethyl cellulose ether is as follows: 10 parts of carboxymethyl cellulose and 1 part of polyvinyl alcohol are mixed to obtain the flexible carboxymethyl cellulose ether.
[0085] Test Case
[0086] The flexibility effect of the flexible carboxymethyl cellulose ether prepared by the present invention is evaluated, and the specific operation process is as follows:
[0087] (1) Weigh 1 part of the sample to be tested and dissolve it in 99 parts of water to prepare a 1% carboxymethyl cellulose aqueous solution.
[0088] (2) Adjust the coating thickness of the coater to 200 μm, evenly coat the above glue solution on the copper foil on the coater, and then dry it in an oven at 120° C. for 5 minutes, take it out and put it in a drying dish to cool to room temperature.
[0089] (3) Take out the dried and cooled electrode, place an A4 paper on the front, and use a round punch to punch out three circular electrode sheets (5 cm in diameter) in different areas.
[0090] (4) Set the oven temperature to 120°C and dry the three punched circular electrodes for 1 hour.
[0091] (5) After drying for 1 hour, measure the warping height of the pole piece, and take the average of the warping heights of the three circular pole pieces as the final result.
[0092] According to the above method, the flexible carboxymethyl cellulose ether prepared in Example 1 is used as the battery negative electrode slurry binder, and the flexible carboxymethyl cellulose ether and carboxymethyl cellulose prepared in Comparative Example 2 are used as the samples to be tested, and the photos of the dried samples are as follows: Figure 3 As shown. Figure 3 In the figure, from left to right are copper foil, copper foil coated with flexible carboxymethyl cellulose prepared in Example 1, copper foil coated with flexible carboxymethyl cellulose ether prepared in Comparative Example 2, and copper foil coated with carboxymethyl cellulose. Figure 3 It can be seen that the flexible carboxymethyl cellulose modified by the method provided by the present invention can greatly improve the warping height of the copper foil compared with carboxymethyl cellulose and direct carboxymethyl cellulose + polyethylene glycol blending, and is even lower than that of adding plasticizer, which can significantly improve the flexibility of carboxymethyl cellulose.
[0093] Application Example 1
[0094] A battery negative electrode slurry, comprising 97 parts of graphite dry powder, 700 parts of pure water, 1.8 parts of SBR and 1.2 parts of the battery negative electrode slurry binder prepared in Example 2; the above components are stirred and mixed to obtain a battery negative electrode slurry;
[0095] The battery negative electrode slurry is coated on copper foil with a coating surface density of 550 g / m 2 , and dried at 120°C to obtain the battery negative electrode.
[0096] Application Example 2
[0097] The difference from Application Example 1 is that the flexible carboxymethyl cellulose ether prepared in Example 8 is used as the binder, and the remaining operations are the same as those in Application Example 1.
[0098] Comparative application example 1
[0099] The difference from Application Example 1 is that the flexible carboxymethyl cellulose ether prepared in Comparative Example 1 is used as a binder, and the remaining operations are the same as those in Application Example 1.
[0100] Comparative Application Example 2
[0101] The difference from Application Example 1 is that the flexible carboxymethyl cellulose ether prepared in Comparative Example 2 is used as a binder, and the remaining operations are the same as those in Application Example 1.
[0102] After the battery negative electrode slurries prepared in Application Examples 1-2 and Comparative Application Examples 1-2 were dried, the battery negative electrodes obtained in Application Examples 1-2 did not have obvious curling and cracking, while Comparative Application Examples 1 and Comparative Application Examples 2 had varying degrees of curling.
[0103] It can be seen from the above results that the flexible carboxymethyl cellulose ether provided by the present invention can significantly improve the flexibility and plasticity of carboxymethyl cellulose. This is because the present invention provides the introduction of flexible segments into the side chains of carboxymethyl cellulose, so that the molecular chains of carboxymethyl cellulose have a certain flexibility, and at the same time reduce the interaction between the carboxymethyl cellulose molecular chains, thereby improving the flexibility of carboxymethyl cellulose; the present invention utilizes linear chain polymer materials to weaken the interaction between the modified carboxymethyl cellulose molecules, thereby enhancing the flexibility and plasticity of the flexible carboxymethyl cellulose ether. Therefore, when the flexible carboxymethyl cellulose ether provided by the present invention is used as a binder in the negative electrode slurry, the surface density of the negative electrode material coating can be significantly improved. In addition, the preparation method of the flexible carboxymethyl cellulose ether provided by the present invention is simple and easy to operate, and can solve the problems of harsh reaction conditions, high cost, and cumbersome preparation process in the carboxymethyl cellulose modification method.
[0104] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A flexible carboxymethyl cellulose ether, comprising carboxymethyl cellulose and a flexible chain segment grafted onto the side chain of the carboxymethyl cellulose; the compound of the flexible chain segment comprises one of a methoxy polyethylene glycol-ethylene oxide copolymer, a C10-C16 halogenated alkane, 2-ethyl alkyl chloroformate, an alkyl chloroformate, ethyl (2R)-2,3-epoxy resin alkyl acid, a chloromethyl alkyl ether and a 2-chloroalkyl chloromethyl ether.
2. The flexible carboxymethyl cellulose ether according to claim 1, characterized in that The grafting rate of the flexible carboxymethyl cellulose ether is 5-25%.
3. The method for preparing the flexible carboxymethyl cellulose ether according to claim 1 or 2, comprising: The carboxymethyl cellulose, the compound of the flexible chain segment and the solvent are mixed and subjected to a grafting reaction to obtain the flexible carboxymethyl cellulose ether.
4. The preparation method according to claim 3, characterized in that: The mass percentage of the carboxymethyl cellulose to the solvent is 1 to 50%.
5. The preparation method according to claim 3, characterized in that: The mass ratio of the carboxymethyl cellulose to the mass ratio of the compound of the soft chain segment is 10:0.5-2.
6. The preparation method according to claim 3, characterized in that: The temperature of the grafting reaction is 50-70°C.
7. The preparation method according to claim 3 or 6, characterized in that: The grafting reaction time is 1 to 10 hours.
8. A battery negative electrode slurry binder, wherein the binder in the battery negative electrode slurry is a flexible carboxymethyl cellulose ether or a mixture of a flexible carboxymethyl cellulose ether and a linear chain polymer material; the flexible carboxymethyl cellulose ether is the flexible carboxymethyl cellulose ether according to any one of claims 1 to 2 or the flexible carboxymethyl cellulose ether prepared by any one of the preparation methods of claims 3 to 7.
9. The battery negative electrode slurry binder according to claim 8, characterized in that: The linear chain polymer material includes one or more of linear polyvinyl alcohol, polyvinyl pyrrolidone, linear polyether and polyacrylic acid.
10. The battery negative electrode slurry binder according to claim 8 or 9, characterized in that: The mass ratio of the flexible carboxymethyl cellulose ether to the linear chain polymer material is 10:0.1-5.
Citation Information
Patent Citations
Preparation method of hydroxyethyl carboxymethyl cellulose
CN102924610A
Agarose modification method
CN109438590A
Flexible carboxymethyl cellulose ether, preparation method thereof, negative pole piece and battery
CN117069869A
Cited By
Carboxymethyl dihydroxypropyl cellulose ether as well as preparation method and application thereof
CN122465036A